Orbital foreign body- Study of a case series - Dasgupta, S; Vats, V; Mittal, K S (Nepalese Journal of Ophthalmology, 2015)
Background: Orbital foreign bodies (OFBs) may remain in the orbital cavity for considerable time and manifest with secondary complications. Objective: To report five consecutive cases of orbital trauma with OFBs, who presented at our institute from Jan 2010 to Dec 2013. Cases: The first case of our series with a non-specific history of injury had a chronic granulomatous discharging sinus in the left upper eyelid and an intact globe. The second case, with an injury to the left lower eyelid following an assault, presented late and the manifestations were similar to that of the first case. The third case, of a road traffic accident, had sustained multiple facial and periocular injuries. The nature of all of three OFBs was uncertain by CT- scan, till surgical exploration. The fourth case had sustained injury to his left eye by a flying metal object. X-ray was sufficient to detect the OFB, but as scleral penetration was associated, management was complex. The fifth case had a nonspecific history of injury and the manifestation was similar to that of the first case. The surgical exploration revealed multiple OFB (wood). Conclusion: The OFBs pose difficult diagnostic and therapeutic challenges. Management of such cases, at times, calls for innovation in decision making and formulation of strategies.